My First Ties with the UP Third World Studies Center - Gaspar, Karl (Kasarinlan: Philippine Journal of Third World Studies; Vol 12 No 3 (1997): Rethinking the Third World, 2007)
Excerpt from the TWSC Forum It was at the early stage of the popular movement against the Marcos dictatorship when first heard about the Third World Studies Center of U.P. Diliman. I was the Executive Secretary of the Mindanao - Sulu Pastoral Conference Secretariat (MSPCS), based in Davao City. The Secretariat was put up by the MSPC in 1971 to facilitate the coordination of the pastoral programs of the dioceses of Mindanao-Sulu. Six years later, the Conference appointed me to head the 25-person Secretariat. Considering the repercussions of "the signs of the times," and the Church's call “to make a preferential option for the poor, deprived and the oppressed,” the Secretariat was tasked to set in place a program to promote human rights, justice and peace.